Cultivating Leadership Attributes In Undergraduate Medical Education: A Mixed Method Study - Fatima, Hareem; Khan, Muhammad Nasir Ayub; Niaz, Mahwish; Durrani, Mahrukh; Irum, Shazia; Sami, Muneeza Aamir (Journal of Rawalpindi Medical College, 2025)
Objective: This research aimed to train undergraduate medical students through a feasible and achievable program and assess the effectiveness of integrating leadership training into the formal curricula of undergraduate medical education, aiming to enhance the development of leadership attributes and behaviours among medical students. Methods: This Mix-Method study including 60 students was conducted in a private medical college of Pakistan. The study participants were randomly selected. 30 participants were trained through the Student Leadership Development Program, whereas 30 constituted the control group. A series of training sessions were conducted. The Leadership Trait Questionnaire was administered during the study for Self, Peers and Mentors assessment. Quantitative data was analysed using SPSS version 26. Descriptive statistics were applied, and numerical variables were described using mean, median and interquartile ranges. The aggregate of traits was assessed for both leaders and control groups. Results showing p-value < 0.5 were considered statistically significant. Qualitative data was compiled from students’ responses to open-ended questions by manual thematic analysis. Result: The results of the study demonstrated that most of the students possessed qualities of effective leaders with similar responses by all three evaluator groups. Traits like articulate, friendly, outgoing, persistent, diligent, trustworthy and sensitive showed significant results (p < 0.5) for peers’ assessment whereas for mentor scores the results were statistically convincing only for items i.e., Friendly and Self-confident. No statistically significance difference was noted between the overall scores of leaders and control groups. However, data analysis of students’ comments to open-ended questions provided information that leadership skills are necessary for successful medical practice and can be learnt with proper guidance given on time. Participants acknowledge that teamwork, communication skills, conflict resolution, and time and stress management as necessary knowledge and skills to develop among undergraduate medical students. Conclusion: This study concluded that leadership skills should be taught and developed at the undergraduate level. Keywords: Leadership, Undergraduate Medical Education.